Heterogeneity of circulating prolactin in the bitch - Gobello, María Cristina (2001)
Different molecular forms of circulating prolactin (PRL) are known to occur in several species. As no such information was available in dogs, we assessed the molecular profile of circulating PRL in bitches. Pooled sera from covertly (CTRL) and overtly pseudopregnant (PSPT) diestrous bitches with high or low (> 10 or < 10 ng·mL-1, respectively) serum PRL (measured by ELISA) were analyzed by Sephadex G-100 and Concanavalin A-Sepharose column chromatography. Four serum PRL fractions were identified and termed big-big, big (> 67 kDa), native (23 kDa) and fragmented (< 20 kDa) PRL. The percentages of these fractions were roughly similar in CTRL and PSPT animals, irrespective of their serum PRL levels (higher in PSPT than in CTRL bitches). A large proportion of glycosylated PRL (between 69 and 100%) was also detected in these sera. We conclude that in dogs, circulating PRL occurs in multiple molecular forms, whose relative abundance is comparable in covertly and overtly pseudopregnant bitches.